Strategy of Audiovisual Translation on Enola Holmes Netflix Movie Subtitle - Violita, Violita; Cholsy, Hayatul (Lingual Journal of Language and Culture; Vol 14 No 2 (2022): Lingual: Journal of Language and Culture, 2022)
The article discusses translation strategies of Audiovisual Translation engaged with the movie on Netflix. The research concentrates on translation strategies involved in the AVT subtitle case of an adventure mystery genre in the Enola Holmes Netflix movie to know the relation of translation strategies with AVT concept. This is an audiovisual translation research in a qualitative descriptive, along with data collecting of English and Indonesian subtitles of Enola Holmes Netflix movie. From the findings, it found nine strategies applied in translating the subtitle of Enola Holmes movie. The result reveals strategies found in translating the subtitle text into Indonesian shows the order from the dominant to the least which are condensation (27%), transfer (25%), paraphrase (24%), deletion (13%), expansion (5%), imitation (5%), resignation (1%), decimation (1%), and transcription (0%). Furthermore, it found two situations of the speech acts equivalency in the English into Indonesian subtitle text are equivalence (98%) and not equivalence (2%). Additionally, all of the translation strategies are helpful to produce the efficient subtitles and deliver the original message properly which also does not cross the line of the rules in AVT.